Evaluation of the electronic record of nursing diagnoses and interventions in a computerized system - Carolina Siqueira Amaral; Sabine de Azevedo; Wagner Longaray de Caldas; Emiliane Nogueira de Souza (Universidade Federal de Santa Maria, 2021)
Objective: to assess the opinion of nurses in regard to the electronic recording of nursing diagnoses and interventions in an information system in the hospital context. Method: cross-sectional study, carried out with nurses using data collected in loco through a questionnaire. Descriptive statistics were used for data collection. Results: 87 nurses were included. From these, 52.9% were satisfied with the electronic records of the Nursing Process (NP), 47.1% believe that registering is easy, 58.6% have some difficulty to identify and select the Nursing Diagnoses (ND), and 60.9% self-evaluate their knowledge about using the NANDA-I taxonomy as regular. The selection, modification, scheduling, or cancellation of interventions were indicated as the most difficult tasks. Conclusion: most nurses are satisfied with the electronic records of the NP. They indicate the selection of the ND as the most difficult stage and evaluate their own knowledge about the taxonomy as medium. The participants mentioned difficulties in the stage of nursing interventions.